Dens invaginatus: diagnóstico y manejo clínico. Revisión de literatura - Vásquez Vereau, Grecia (2024)
Dens invaginatus (DI) is a dental alteration that occurs before mineralization and is a consequence of the folding of the enamel organ within the dental papilla. Its characteristics allow the onset and rapid progression of carious lesions and, consequently, pulp and periapical disease.  This article summarizes data from original articles and literature reviews from the Scopus/PubMed database. Therefore, the aim of the present literature review is to expose guidelines for the clinical management of Dens invaginatus according to its etiology, classification and diagnosis, thus representing an improvement in the effectiveness of the treatment and prognosis of these very complex alterations.